Priority of Early Colonizers but No Effect on Cohabitants in a Synergistic Biofilm Community - Olsen, Nanna Mee Coops; Røder, Henriette Lyng; Russel, Jakob; Madsen, Jonas Stenløkke; Sørensen, Søren Johannes; Burmølle, Mette (Frontiers in Microbiology, 2019)
The arrival order of different species to a habitat can strongly impact community assembly and succession dynamics, thus influencing functionality. In this study, we asked how prior colonization of one community member would influence the assembly of a synergistic multispecies biofilm community grown in vitro. We expected that the prior arrival would confer an advantage, in particular for good biofilm formers. Yet, we did not know if the cohabitants would be impaired or benefit from the pre-colonization of one member, depending on its ability to form biofilm. We used a consortium consisting of four soil bacteria; Stenotrophomonas rhizophila, Xanthomonas retroflexus, Microbacterium oxydans and Paenibacillus amylolyticus. This consortium has been shown to act synergistically when grown together, thus increasing biofilm production. The results showed that the two good biofilm formers gained a fitness advantage (increase in abundance) when allowed prior colonization on an abiotic surface before the arrival of their cohabitants. Interestingly, the significantly higher number of the pre-colonized biofilm formers did not affect the resulting composition in the subsequent biofilm after 24 hours.